UMKM Class Determination Support System Using Profile Matching - Setiawansyah Setiawansyah; Adhie Thyo Priandika; Bustanul Ulum; Ade Dwi Putra; Dyah Ayu Megawaty (PDSI, 2022)
UMKM are businesses run by individuals, households, or small business entities. The classification of MSMEs is usually carried out with limits on turnover per year, the amount of wealth or assets, and the number of employees. Determining the UMKM class using the profile matching method which can make effective decisions on existing problems. With the decision support system to determine the class of UMKM in determining the class of UMKM by looking at the highest value of the ranking results based on several aspects of the assessment including turnover, assets, human resources, marketing, and permits. The results of the calculation for the assessment of the Micro UMKM class for PT Hasta Karya Nugraha are 1.5275 for the Micro UMKM Class Appropriate because it passes the minimum standard value for Micro MSMEs, the Small MSME Class for PT Hasta Karya Nugraha is 2.2975 Appropriate because it passes the minimum standard value for Small UMKM, and The Small UMKM class for PT Hasta Karya Nugraha is 2.3 Not suitable because it does not pass the minimum standard value for Medium UMKM. As for the results of the calculation of the assessment of the Micro UMKM class for CV Permata Jaya, namely 0.54 the Micro MSME Class is Appropriate because it passes the minimum standard value for Micro MSMEs, the Small UMKM Class for CV Permata Jaya is Appropriate because it passes the Small MSME minimum standard value, and the Small UMKM Class for CV Permata Jaya. CV Permata Jaya which is 1.62 Appropriate because it passes the minimum standard value of Medium UMKM. The conclusion of the assessment results of the application of the profile matching method to determine UMKM to move up the class for PT Hasta Karya Nugraha is in the Micro class, and CV Permata Jaya is in the Middle class.